Маркетинг: учебное пособие / Т. Н. Парамонова - Парамонова Т.Н. (Среднее профессиональное образование, 2008)
Экземпляры: 7ф. (21.01.09) / Инвентарный номер: 44835 / Цена: / Сис.шифр: 65.290-2 / Авт.знак: П18 / ББК: 65.290-2